2005
DOI: 10.1163/156856205774269494
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of collagen gels derived from rats of different ages

Abstract: In a previous study, we found that different collagen gels produced using collagen fibrils extracted from 1-, 4- and 8-month-old rat tails essentially influenced the morphogenesis of epithelial cells. More importantly, the youngest collagen gel induces the highest level of cell apoptosis. The objective of this study was to investigate mechanical properties of various collagen gels correlated to the rat ages. A rheometer and dynamic mechanical analyzer were used to measure shear and compressive properties of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 24 publications
3
31
2
2
Order By: Relevance
“…21 Plastic compression therefore yields scaffolds much denser than conventional, uncompressed collagen type I matrices. The moduli of these conventional scaffolds are typically below 1 kPa, 22,23 and these scaffolds should first grow stronger in culture. 21 Our technique of plastic compression differs from earlier studies, because we use cell culture inserts with 3 mm pores to reduce the liquid content instead of nylon and stainless steel meshes.…”
Section: Discussionmentioning
confidence: 99%
“…21 Plastic compression therefore yields scaffolds much denser than conventional, uncompressed collagen type I matrices. The moduli of these conventional scaffolds are typically below 1 kPa, 22,23 and these scaffolds should first grow stronger in culture. 21 Our technique of plastic compression differs from earlier studies, because we use cell culture inserts with 3 mm pores to reduce the liquid content instead of nylon and stainless steel meshes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although immunofluorescence detection for Type-I and Type-III collagen did not show substantial differences at the protein level between young and old prostate tissue, confocal microscopy revealed a disorganized collagen matrix in the aged prostate microenvironment when compared to young prostate (Figure 6b). Previous studies have demonstrated the effect of fibrillar collagen and substrate rigidity on epithelial cell proliferation, apoptosis, and motility in culture systems, suggesting a direct role of the collagen network on the behavior of epithelial cells (8)(9)(10). Taken together, we hypothesized that the disorganized collagen matrix and the diminished expression of Col1a2 and Col3a1 in the aged prostate microenvironment may have an effect on the structural and signaling properties of the extracellular matrix.…”
Section: Bodymentioning
confidence: 74%
“…Billiar (2011) report testing AFM for this purpose, but they could not measure differences between polymerized and nonpolymerized collagen. A surface tension-induced artefact is mentioned in a comment from Wu et al (2005) for application of dynamic mechanical analysis of hydrated collagen gels. Our own observations allow the same conclusion.…”
Section: Determining the Elastic Modulus Using Afmmentioning
confidence: 99%
“…• C. To avoid bias by surface tension at the hydrogel to air interface (Wu et al, 2005), all measurements were conducted with the cantilevers submerged in preheated phosphate-buffered saline (PBS). Force spectroscopy measurements were conducted using silicon-nitride cantilevers (CSC38, Mikromasch) with force constants ranging from 0.03 to 0.08 N m −1 and quasi-conical tips with an opening angle between 34…”
Section: Determining the Elastic Modulus Using Afmmentioning
confidence: 99%